Position Tracking Optimization For An Electro-Hydraulic Actuator System - Rozaimi, Ghazali (Universiti Teknikal Malaysia Melaka, 2016)
Electro-hydraulic actuator (EHA) system has received a positive admission and widely utilized in the industrial field for the process such as lifting,clamping and pressing.It is well known that the EHA system is exposed to the disturbances,uncertainties,and parameter variations which are caused by various factors for instance the changes in load or total moving mass,supply pressure, friction and leakage coefficient.These problems consequently pose to a great challenge in EHA system modelling and controller development in order to achieve a good performance in the system positioning control.In this paper,a comparative study in different trajectories that represents the desired positioning which are multi-step and multi-sine reference signal is applied to the system in order to access the capability of the proportional-integral-derivative (PID) controller that is tuned by using the Ziegler-Nichols (ZN) and Particle Swarm Optimization (PSO) tuning methods.The finding shows that the PID controller variables obtained through the PSO tuning method performs better than the conventional ZN tuning method.From the simulation study,it can be concluded that the PSO technique was able to obtain a better PID controller parameter and provides a much satisfying positioning tracking capability.